Acute Graft-Versus-Host Disease After Humanized Anti-CD19-CAR T Therapy in Relapsed B-ALL Patients After Allogeneic Hematopoietic Stem Cell Transplant - Liu, Pengjiang; Liu, Meijing; Lyu, Cuicui; Lu, Wenyi; Cui, Rui; Wang, Jia; Li, Qing; Mou, Nan; Deng, Qi; Yang, Donglin (Frontiers in Oncology, 2020)
We studied the acute graft-versus-host disease (GVHD) after humanized anti-CD19-CAR T therapy in relapsed B-acute lymphoblastic leukemia (ALL) patients after allogeneic hematopoietic stem cell transplant (allo-HSCT). Fifteen B-ALL patients were enrolled in our study. Thirteen patients (86.67%) achieved a complete response (CR) or CR with incomplete count recovery. The donor chimerism of the 13 patients reached 99.86 ± 0.21%. The development of aGVHD was observed in 10 patients (66.67%). Six patients developed grade I-II of aGVHD, while the other four patients developed grade III-IV of aGVHD. The notable adverse events were grade 1–2 cytokine release syndrome (CRS) in 10 patients and grade 3–4 CRS in five patients. Two patients died of infection, while another patient died of sudden cardiac arrest. The anti-CD19-CAR T cells were not eliminated in peripheral blood when the patients developed aGVHD. However, we did not observe their expansion peaks again in the process of aGVHD. During the aGVHD, the peaks of IL-6 and TNF-a were correlated with aGVHD levels. By May 31, 2020, the rates of leukemia-free survival (LFS) and overall survival (OS) at 180 days were 53.846 and 61.638%, respectively. All the patients who survived to date experienced aGVHD after humanized anti-CD19-CAR T cell therapy. Trial registration: The patients were enrolled in clinical trials of ChiCTR-ONN-16009862 and ChiCTR1800019622.